Peningkatan Kemampuan Matematika Siswa dalam Pembinaan Olimpiade MIPA SD di Gugus Ahmad Yani Kuningan - Abdul Rosyid; Muhammad Noor; Atang Sutisna (Universitas Mathla'ul Anwar Banten, 2020)
IMPROVEMENT OF STUDENTS’ MATHEMATICAL ABILITIES IN COACHING THE MATHEMATICS AND NATURAL SCIENCE OLYMPICS IN THE AHMAD YANİ KUNİNGAN CLUSTER. To participate in the Mathematics Olympics elementary school activities, school lessons are not enough. Students must have more experience, especially non-standard questions. This article aims to examine the improvement of students' mathematical abilities in coaching the Mathematics and Natural Sciences Olympics in the Ahmad Yani Kuningan Cluster. Coaching methods include planning, implementing, and evaluating. The results of this activity are the mathematical abilities of elementary school students increase from the pretest results to the posttest results with an average increase in N-Gain of 0.67. As many as 50% of the activity participants achieved a high category increase and another 50% achieved a medium category increase. With this coaching activity, elementary school students in the Ahmad Yani Cluster have improved their mathematical abilities so that they are ready to take part in the Mathematics Olympics at District, Provincial, and National levels.